The Analysis Of Multicultural Personality And Intercultural Competency On Expatriates’ Cross-Cultural Adjustment - Shuib, Awang Rozaimie Awang (2013)
The present study was designed to predict multicultural personality and intercultural competency (intercultural awareness, intercultural sensitivity and intercultural adroitness) on expatriates’ cross-cultural adjustment (psychological and sociocultural), its differences between foreign expatriates in Malaysia and Malaysian Expatriates Overseas, and between Self-initiated Expatriates and Assigned Expatriates. A cross-sectional investigation was carried out through web-survey, postal and drop-off method. A purposive sampling technique was used to extract respondents from several directories and websites. Six months were taken to obtain sufficient number of responses (minimum 440 cases) where 476 responses obtained but only 427 responses are usable. Five adopted and one adapted scales have been used to measure the contended hypotheses using Variance-based Partial Least Square (PLS) procedures. The data was analysed by using SmartPLS software due to its powerful ability to maximize the prediction of structural model and the dependent variable was skewered. The key findings demonstrated that openmindedness, social initiative, emotional stability, similarity awareness, interaction confidence, interaction attentiveness, interaction management and interaction relaxation were found to predict expatriates’ cross-cultural adjustment.